Logistic overloads on the import of new vehicles from Toyota 2013-2017 - Santome Jiménez, Basilia Jessica (2019)
Objective: To carry out an investigation on the main logistic cost overruns concerning the importation of new Toyota vehicles in order to minimize the impact on customs procedures. Method: A non-experimental scientific research was used since it is a topic related to the social sciences. For that reason, the theories shown as scientific were used for the support of this research. The type of research design is correlational since the effects of one variable on the other were examined. To achieve this objective, information was also used from surveys of 35 people who work both in the same Toyota company, as well as in the customs agency that carries out the dispatches. Results: The main logistic cost overruns are determined at the customs office of import of vehicles in the Toyota company, presenting cost overruns for 80% delays and at the port terminal in terms of risks representing 20% of the cost overruns. Conclusions: This work will be useful for future analysis studies related to issues of efficiency, productivity and continuous improvement in customs clearance procedures, to be aligned with the guidelines proposed by the main international organizations such as the World Customs Organization (WCO), the World Trade Organization (WTO) and The Andean Community (CAN).